3D-printable CFR polymer composites with dual-cure sequential IPNs. (17th May 2016) - Griffini, Gianmarco; Invernizzi, Marta; Levi, Marinella; Natale, Gabriele; Postiglione, Giovanni; Turri, Stefano
Abstract: In this work a sequential interpenetrating polymer network (IPN) obtained by co-formulation of a photocurable acrylic resin with a thermocurable epoxy resin is presented and proposed as matrix for the fabrication of carbon-fiber reinforced (CFR) composite structures by means of 3D-printing technology. This approach combines the advantages of the easy free-form fabrication typical of the 3D-printing technology with the purposely customized features of the newly developed IPN material. Photocalorimetric and dynamic-mechanical analyses were performed in order to investigate the photo- and thermal-crosslinking reactions and their effect on the development of the IPN system. The IPN resin was finally loaded with carbon fibers and successfully ultraviolet-assisted (UV)-3D printed, demonstrating the possibility of fabricating CFR composite materials in 3D with excellent mechanical properties. Being the first example of direct fabrication of IPN-based composites by 3D printing, this study clearly shows the great potential of this additive manufacturing technology for advanced industrial applications. Graphical abstract: